Unit-based emissions and environmental impacts of industrial condensable particulate matter in China in 2020. (September 2022) - Wang, Kun; Gao, Jiajia; Liu, Kaiyun; Tong, Yali; Dan, Mo; Zhang, Xiaoxi; Liu, Chunlei
Abstract: The emission of condensable particulate matter (CPM) and its environmental impacts are arousing concern in China with the effective control of filter particulate matter (FPM). This study established an up-to-date and unit-based CPM emission inventory for industrial sectors and systematically evaluated the effects of CPM on primary and secondary PM2.5 in China. In 2020, the national CPM emissions total for industrial sectors was estimated to be 0.98 Tg with uncertainty from −49% to 66%, including 0.62 Tg of organic CPM (CPMorg ) and 0.36 Tg of inorganic CPM (CPMin ). Totals of 62%, 23% and 8% CPM were emitted from coal-fired power plants, coal-fired industrial boilers and sinter plants, respectively. By filling CPM emissions in PM2.5 simulation, the normalized mean bias (NMB) of model to observation was improved from −27% to −14% in East, North and Central China. The 4 μg/m 3 PM2.5 concentration was attributed to CPM emissions in this region, accounting for 10% of observations. On "polluted" days (PM2.5 >75 μg/m 3 ), industrial CPM emissions can contribute 7 μg/m 3 PM2.5 in North China. Therefore, China should focus on controlling CPM from coal combustion to ensure continuous air quality improvement. Graphical abstract: Image 1 Highlights: An up-to-date and unit-based emission inventory for industrial sectors established. Coal-fired sources and sinter plants are the key sectors for CPM emissions. The effects of CPM on primary and secondary PM2.5 in China cannot be neglected.